Cardamom supplementation improves inflammatory and oxidative stress biomarkers in hyperlipidemic, overweight, and obese pre‐diabetic women: a randomized double‐blind clinical trial. (17th July 2017) - Kazemi, Shiva; Yaghooblou, Fatemeh; Siassi, Fereydoun; Rahimi Foroushani, Abbas; Ghavipour, Mahsa; Koohdani, Fariba; Sotoudeh, Gity
Abstract: BACKGROUND: Several preclinical studies have shown that spices may decrease the risk of chronic diseases. However, it has been suggested that more clinical trials be carried out to strengthen this preclinical evidence. The purpose of the present study was to evaluate the effects of cardamom ( Elettaria cardamomum ) supplementation on inflammation and oxidative stress in hyperlipidemic, overweight, and obese pre‐diabetic women. METHODS: This randomized, placebo‐controlled, double‐blind clinical trial was conducted on 80 pre‐diabetic subjects. They randomly received the cardamom supplement ( n = 40, 3 g d −1 ) or identical inert placebo ( n = 40) for 8 weeks. Serum concentrations of high‐sensitivity C‐reactive protein (hs‐CRP), interleukin‐6 (IL‐6), tumour necrosis factor α, total antioxidant capacity, malondialdehyde (MDA), protein carbonyl, and erythrocyte superoxide dismutase and glutathione reductase activity were analyzed at the baseline and after intervention. RESULTS: After the adjustment of some covariates, cardamom supplementation significantly decreased serum hs‐CRP ( P = 0.02), hs‐CRP:IL‐6 ratio ( P = 0.008), and MDA ( P = 0.009) compared with the placebo group. CONCLUSION: Cardamom could improve some parameters of inflammation and oxidative stress in pre‐diabetic subjects. Thus it may be useful in reducing complications associated with inflammation and oxidative stress in these patients. Copyright © 2017 Society of Chemical Industry © 2017 Society of Chemical Industry